Capping nanoparticles with graphene quantum dots for enhanced thermoelectric performance1. Issue 7 (15th July 2015) - Liang, Yuantong; Lu, Chenguang; Ding, Defang; Zhao, Man; Wang, Dawei; Hu, Chao; Qiu, Jieshan; Xie, Gang; Tang, Zhiyong
<x xml:space="preserve">Abstract</x> The general capability of graphene quantum dots to serve as capping ligands exchanging native organic stabilizers for various types of semiconductor nanoparticles affords the opportunity to engineer functional nanocomposites with remarkable thermoelectric properties.